Application of Wedge Fracture Test for Texture Analysis in Boiled Sweetpotato (Ipomoea batatas) - Banda, Linly; Moyo, Mukani; Nakitto, Mariam; Swanckaert, Jolien; Onyango, Arnold; Magiri, Esther; Muzhingi, Tawanda (African Journal of Food Science, 2021)
Several instrumental texture analysis methods have been developed for use in sweetpotato. However, there are very few reports on the use of the wedge fracture test. The purpose of the study was to develop a texture analysis method using a wedge fracture and evaluate its performance against compression test in assessing sweetpotato varieties with different cooking times. The optimal cooking time (OCT) of five sweetpotato varieties was determined by boiling 2.5 cm3 cubes until soft. Samples for texture analysis were prepared under four conditions: 85°C for 10 and 15 min; and 95°C for 5 and 10 min. Peak positive force (firmness) and total work done (toughness) were determined using the wedge fracture texture analysis. The correlation between the OCT and texture measurements was evaluated, and samples incubated at 85°C for 15 min had the highest correlation with OCT (R2 = 0.725). Using this heat treatment, texture measurements from the wedge fracture were compared to those obtained from a compression test. The wedge fracture test gave significant discrimination of sweetpotato varieties (p ≤ 0.05) while the compression test did not. The wedge fracture test is thus recommended for determining the instrumental firmness of boiled sweetpotato varieties with different cooking times.
Keywords: Texture; Optimal cooking time; Wedge fracture test; Orange-fleshed sweetpotato